Peningkatan Hasil Belajar Tematik Terpadu Peserta Didik Menggunakan Metode Problem Based Learning di Sekolah Dasar - Utama, David Pra; Muhammadi, Muhammadi (Universitas Negeri Padang, 2022)
This study aims to determine the increase in integrated thematic learning outcomes of students in class V of Primary Schools using the Problem Based Learning (PBL) model. This type of research is classroom action research, which was conducted in two cycles. The approach taken in this study is a qualitative approach and quantitative approach. The observations of the Learning Implementation Plan in the first cycle obtained an average of 87.49% good qualifications (B), and experienced an increase in the second cycle so as to obtain an average of 96.42% with very good qualifications (AB). In the implementation of the first cycle learning aspects aspects of teachers and students each gained an average of 78% with good qualifications (C), and in the second cycle increased to 96% very good qualifications (AB). In the aspect of knowledge and skills of students in cycle I obtained an average of 74.36 with a good predicate (B), and also an increase in cycle II so as to obtain an average of 88.33 with a very good predicate (A). This shows an increase in student learning outcomes in integrated thematic learning using the Problem Based Learning (PBL) model in class V SDN 01 Bandar Buat City of Padang.